The impact of zinc pre-exposure on ciprofloxacin resistance development in E. coli - Suprenant, Mark P.; Ching, Carly; Gross, Neila; Sutradhar, Indorica; Anderson, Jessica E.; El Sherif, Nourhan; Zaman, Muhammad H. (Frontiers in Microbiology, 2024)
IntroductionAntimicrobial resistance (AMR) is a global health crisis that is predicted to worsen in the coming years. While improper antibiotic usage is an established driver, less is known about the impact of other endogenous and exogeneous environmental factors, such as metals, on AMR. One metal of interest is zinc as it is often used as a supplement for diarrhea treatment prior to antibiotics.Materials and methodsHere, we probed the impact of zinc on ciprofloxacin resistance in E. coli via altering zinc exposure time and order. We found that the order of exposure to zinc impacted resistance development. These impacted samples then underwent whole genome and RNA sequencing analysis.ResultsZinc pre-exposure led to a subsequent acceleration of ciprofloxacin resistance. Specifically, we saw that 5 days of zinc pre-exposure led samples to have nearly a 4× and 3× higher MIC after 2 and 3 days of subinhibitory antibiotics, respectively, compared to samples not pre-exposed to zinc, but only if ciprofloxacin exposure happened in the absence of zinc. Additionally, for samples that underwent the same pre-exposure treatment, those exposed to a combination of zinc and ciprofloxacin saw delayed ciprofloxacin resistance compared to those exposed to only ciprofloxacin resulting in up to a 5× lower MIC within the first 2 days of antibiotic exposure. We did not observe any genetic changes or changes in antibiotic tolerance in cells after zinc pre-exposure, suggesting changes in gene expression may underlie these phenotypes.DiscussionThese results highlight the need to reexamine the role of zinc, and supplements more broadly, on antibiotic resistance evolution.